MULTIPLEX POLYMERASE CHAIN REACTION (PCR) FOR THE DETECTION OF NEISSERIA GONORRHOEAE AND THE QUINOLONE RESISTANCE GENE IN PAKISTAN - Waseem, Hafsa; Naeem, Afnan; Ali, Sakhawat; Sarfraz, Sharjeel; Usman, Javaid; Gilani, Mehreen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To detect Neisseria gonorrhoeae from the urine of male patients reporting with active urethral discharge using multiplex polymerase chain reaction (PCR). And the simultaneous detection of the quinolone resistance determining region (QRDR) on the Neisseria gonorrhoeae gene using multiplex polymerase chain reaction.Study Design: Cross sectional study.Place and Duration of Study: Microbiology department, Army Medical College Rawalpindi Pakistan, from Mar to Dec 2018.Methodology: Male patients with active urethral discharge with no past history of antibiotic use for urethral discharge were included in study and patients without active urethral discharge and history of antibiotic use for urethral discharge were excluded. Urine of patients of active urethral discharge was collected and multiplex polymerase chain reaction was done by using two forward primers along with common reverse primer.Results: In this study 24 (40%) of patients who presented with active urethral discharge were positive for gonorrhea. However Quinolone Resistance Determining Region is detected in 17 (70.83%) of cases and only 7 (29.17%) were sensitive to ciprofloxacin.Conclusion: The multiplex polymerase chain reaction is very efficient and effective method for the simultaneous detection of Neisseria gonorrhoeae and status of isolate susceptibility to ciprofloxacin. And in Pakistan ciprofloxacin cannot be used as first line drug for the treatment of gonorrhea.